Monitoring of Federal Criminal Convictions and Sentences: Appeals Data, 1999 ([Verlag nicht ermittelbar], 2001)
This collection contains appellate information from the 12 circuit courts of appeals of the United States. The United States Sentencing Commission compiled from the Clerk of the Court of each court of appeals the final opinions and orders, both published and unpublished, in all criminal appeals for the time period surveyed. The Commission also collected habeas corpus decisions (although technically civil matters), because such cases often involve sentencing issues. Both the "case" and the "defendant" are used in this collection as units of analysis. Each "case" comprises individual records representing all codefendants participating in a consolidated appeal. Each defendant's record comprises the sentencing-related issues corresponding to that particular defendant. The 1999 data includes all appeals cases received as of December 27, 1999, that had disposition dates between October 1, 1998, and September 30, 1999 (inclusive).